Pola Kalimat Bahasa Indonesia pada Suami Bule dalam Interaksi Pasangan Lintas Budaya Indonesia-Paris - Putri, Yusriani Febrian Ramadani; Nurhadi, Nurhadi; Roekhan, Roekhan (P3M Politeknik Negeri Media Kreatif, 2025)
Indonesian sentence patterns of Caucasian husbands in cross-cultural couple interactions are influenced by the first language of their home country. Cross-cultural couples, involving native Indonesian speakers and foreign speakers, provide an overview of the process of how Indonesian is learned, and used in communication by foreign speakers to native speakers. This research uses a qualitative descriptive approach. The data collection technique of this research is through: 1) searching for video data sources, 2) selecting appropriate videos, 3) recording data, 4) identifying data, 5) rechecking, and drawing conclusions. The data source is from TikTok videos of @opiiyn and @opidiparis accounts. The results of this study show that first language influences the acquisition or learning process and the use of Indonesian as a second language of foreign speakers. The first language (B1) of the Caucasian husband (Raf) based on the data obtained through this study is French, which shows a significant influence on the acquisition of the second language (B2), namely Indonesian in daily communication with his wife (Opi). Syntactically, sentence pattern (SPO), noun + adjective, complex conjunction, phonology, mixture of languages in one sentence, and intonation.